Kinetics of lower limb joints during forehand loops with alternating and full-foot support patterns in table tennis - Jin, P.; Yang, C.; Bankosz, Z.; Sun, B.; Kong, Q.; Ren, J. (Sports Biomechanics, 2026)
Footwork plays a crucial role in the stroke performance of athletes, yet its underlying foot support patterns remain underexplored. This study aimed to compare the biomechanical differences in lower limb joints between alternating foot support pattern (ASP) and full-foot support pattern (FSP) in table tennis footwork. Twelve national level I male table tennis athletes participated in a within-subject design, performing both foot support patterns. Compared with ASP, FSP showed significantly lower peak hip power generation (10.38 ± 1.42 W/kg), lower ankle power generation and absorption, with reduced ankle rates of change. In addition, the relative contribution of ankle power generation (1.25 ± 1.60%) decreased, leading to a higher combined contribution of the hip (93.62 ± 3.76%) and ankle (4.96 ± 4.46%) joints. The peak time of ankle power absorption was significantly delayed. By contrast, the relative contributions of hip and knee power generation were higher in FSP than in ASP. Overall, hip joint function serves as the primary source of positive work in both ASP and FSP. FSP reduced ankle joint contribution, with the hip and knee joints compensating for this limitation during the stroke. Athletes should actively adjust their movements according to the characteristics of the foot support pattern.